Supply chain production planning of a manufacturing project system 4.0: case study: Shipbuilding. Issue 1 (October 2021) - Ramirez, M; Pérez, V; Gómez, A; Montaño, R; Batista, M
Abstract: Projects characterized by high difficulty in terms of planning and administrative control, require the strategies facilitated by Manufacturing Project Systems (MPS). Among them is an adequate management of the Supply Chain used as a competitive strategy. It could be said that in the case of shipbuilding, the Supply Chain is much more complicated due to the number of intervening parties and many shipyards have opted to include Concurrent Engineering with the implication of considering all the elements that make up the product life cycle. The objective of this article is based on the study of the existing applications for the integration of the companies' management as well as the technological contributions that can collaborate to the integration of the Supply Chain production planning. Getting to identify the seven key technologies of Industry 4.0 that most contribute to the sustainability of shipbuilding.